Pengaruh Pelatihan dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Extrupack Bekasi - Nur Kamilah Aprilia; Sugeng Suroso; Ery Teguh Prasetyo (Universitas 45 Surabaya, 2024)
This study aims to determine whether there is an effect of Job Training and Discipline on Employee Performance at PT Extrupack Bekasi. The method used in this research is quantitative method. The population in this study amounted to 220 people. The sampling technique used simple random sampling technique. The sample in this study amounted to 142 respondents obtained from calculations using the slovin formula. The data collection technique was by distributing questionnaires and processed using the SPSS version 27 application. This study uses multiple linear regression analysis, and hypothesis testing using the t test and F test. The results showed that in the partial test (t) the training variable had an effect on employee performance with a t value of 5.452> t table 1.977 and a sig value. 0.000 <0.05, work discipline variables affect employee performance with a t value of 6.479> t table 1.977 and sig value. 0.000 <0.05, and the results of the simultaneous test (F) training and work discipline variables affect employee performance with the value of F count 69.141> F table 3.06 and sig value. 0,000 < 0,05.